Risk Factors for Multidrug Resistant Organisms in Exacerbation of Bronchiectasis (Chest & Heart Journal, 2021)
Background & Objective: Bronchiectasis is a chronic debilitating airway disease. Patients with bronchiectasis are prone to repetitive infective exacerbations. Antibiotics are considered the cornerstone in the management of exacerbations. Frequent treatment with antibiotics makes the organism much more susceptible to acquire antibiotic resistance that account for a substantial number of excess deaths and catastrophic healthcare spending. Attention in focusing the risk factors for antibiotic resistance is necessary to take steps to reduce the development of resistant organisms and framing antibiotic policy.Patients & Methods: This cross-sectional observational and analytical study was conducted in the Inpatient Department of Respiratory Medicine in National Institute of Diseases of the Chest and Hospital from April 2019 to April 2020. A total of 202 adult patients with exacerbation of bronchiectasis were enrolled. Early morning Sputum were examined for bacteriological culture and sensitivity. Multidrug-resistance was determined according to European Centre of Disease Prevention and Control classification.Result: Two hundred and two exacerbations were included and microorganisms were isolated in 155 cases. Pseudomonas aeruginosa 87(55.8%) and Klebsiella pneumoniae 53(34.0%) were more frequent. Multidrug-resistant pathogens were found in 90(58.1%) cases. In multivariate analysis, recent hospitalization (Odds ratio (OR)2.42,95% CI 1.03-5.71), frequent antibiotic use (OR 2.650, 95% CI 1.21-5.80) and chronic kidney disease (5.98,95%CI 1.57-22.81) were found to be independent predictors for MDR pathogens.Conclusion: Recent hospitalization, frequent antibiotic use and chronic kidney disease were seemed to be the risk factor for multidrug resistant bacteria. Identification of the factors associated with antibiotic resistance helps in rational prescription of antibiotics.Chest Heart J. 2020; 44(2) : 89-95